The Influence of Principal’s Role, Work Motivation, and Work Culture on the Performance of Junior High School Teachers - Kuncoro, Joko; Ysh, A.Y Soegeng; Bunyamin (IQRO: Journal of Islamic Education, 2024)
This study aims to analyze the effect of the principal's role, work motivation, and work culture on the performance of teachers in junior high schools in the Kandangan District, Temanggung Regency. The research uses a quantitative approach with a survey method. The population of this study consists of 105 junior high school teachers from five schools in the Kandangan District, with a saturated sampling technique. Data were collected through questionnaires measuring the variables of the principal's role, work motivation, work culture, and teacher performance. Data analysis was performed using multiple linear regression analysis. The results show that the principal's role, work motivation, and work culture significantly affect teacher performance, with a total contribution of 73.5%. An effective principal's role, high motivation, and a positive work culture are necessary to improve teacher performance. Keywords: Principal's Role; Work Motivation; Work Culture; Teacher Performance.